Prehistory Down Under : archaeological investigations of submerged Aboriginal sites at Lake Jasper, Western Australia - Dortch, Charles
Much of Australian prehistory lies under water. Although confined to the continent's extreme southwestern corner, field studies described in this report show that this submerged prehistoric component is very real, with numerous archaeological sites and former land surfaces awaiting investigation on the floors of Australia's lakes, rivers and estuaries, and on its submerged continental margins.